Design, synthesis and biological evaluation of matrine derivatives as potential anticancer agents. Issue 4 (15th February 2018) - Li, Zheng; Luo, Mengyang; Cai, Bin; Wu, Lichuan; Huang, Mengtian; Haroon-Ur-Rashid,; Jiang, Jun; Wang, Lisheng
Graphical abstract: Highlights: 58 matrine derivatives with novel structures were synthesized and characterized. All of the derivatives exhibited improved anti-cancer effects than matrine. A6 induce apoptosis and arrest CNE2 and SMMC-7721 cells at G2/M phase. B21 induce apoptosis. Abstract: Using matrine (1 ) as the lead compound, a series of new 14-( N -substituted-2-pyrrolemethylene) matrine and 14-( N -substituted-indolemethylene) matrine derivatives was designed and synthesized for their potential application as anticancer agents. The structure of these compounds was characterized by 1 H NMR, 13 C NMR and ESI-MS spectral analyses. The target compounds were evaluated for their in vitro cytotoxicity against three human cancer cell lines (SMMC-7721, A549 and CNE2). The results revealed that compound A6 and B21 displayed the most significant anticancer activity against three cancer cell lines with IC50 values in range of 3.42–8.05 μM, which showed better activity than the parent compound (Matrine) and positive control Cisplatin. Furthermore, the Annexin V-FITC/PI dual staining assay revealed that compound A6 and B21 could significantly induce the apoptosis of SMMC-7721 and CNE2 cells in a dose-dependent manner. The cell cycle analysis also revealed that compound A6 could cause cell cycle arrest of SMMC-7721 and CNE2 cells at G2/M phase.